Evaluating the function,f(x) = –2x² – 3x + 5 for x = -3, we would have: f(-3) = -4. (option B).
To evaluate a function, plug in the given value of the input (x) and simplify.
Thus:
f(x) = –2x² – 3x + 5
Substitute x = -3 into the function
f(-3) = –2(-3)² – 3(-3) + 5
f(-3) = -2(9) + 9 + 5
f(-3) = -4
Therefore, evaluating the function,f(x) = –2x² – 3x + 5 for x = -3, we would have: f(-3) = -4. (option B).
Learn more about evaluation of function on:
Answer:
The correct answer is -4.
Step-by-step explanation:
have a good day yall
Answer:
A = 4 cm^2
Step-by-step explanation:
The area of a triangle is
A = 1/2 b*h
The base is 4 and the height is 2
A = 1/2 ( 4*2)
A = 1/2*8
A = 4 cm^2
Answer:
4
Step-by-step explanation:
A = BH/2
or Area = Base multiplied by Hieght divided by 2.
(b)4 x (h)2 = 8
8/2 = 4
Perform the operation. Write the answer in standard form.
1. (6 − i) + (9 + 5i)
2. (7 + 3i) + (11 + 2i)
3. (12 + 4i) − (2 − 15i)
4. (3 − 7i) − (3 + 5i)
5. 7 − (2 − 3i) + 6i
6. −16 + (3 + 4i) − 4i
7. 3i(6 − 5i)
8. −2i(8 + 2i)
9. (−5 + i)(8 − 6i)
10. (3 − 6i)(−1 + 7i)
11. (2 + 5i)(2 − 5i)
12. (−3 − i)(−3 + I)
13. (4 + i) 2
14. (5 − 9i) 2
Thank you again <3
Answer:
1.
2.
3.
4.
5.
6.
7.
8.
9.
10.
11.
12.
13.
14.
Step-by-step explanation:
Standard form means to put the terms in order based on their exponent (x³ -> x² -> x -> constant)
1. (6 - i) + (9 + 5i)
2. (7 + 3i) + (11 + 2i)
3. (12 + 4i) - (2 - 15i)
4. (3 - 7i) - (3 + 5i)
5. 7 - (2 - 3i) + 6i
6. -16 + (3 + 4i) - 4i
7. 3i(6-5i)
8. -2i(8+2i)
9. (-5 + i)(8 - 6i)
10. (3 - 6i)(-1 + 7i)
11. (2 + 5i)(2 - 5i)
12. (-3 - i)(-3 + i)
13. (4 + i) * 2
14. (5 - 9i) * 2
:p when I first started answering this I thought the parentheses were being multiplied every time and did 100x more work .-.
Hope it helps <3 :D
Answer:
58 feet
Step-by-step explanation:
Just finished this lesson and checked the answer key.